Perpendicular MXene Arrays with Periodic Interspaces toward Dendrite‐Free Lithium Metal Anodes with High‐Rate Capabilities. (11th November 2019) - Cao, Zhenjiang; Zhu, Qi; Wang, Shuai; Zhang, Di; Chen, Hao; Du, Zhiguo; Li, Bin; Yang, Shubin
Abstract: Although lithium metal is an ultimate anode material for lithium‐based batteries owing to its high theoretical capacity, the uncontrollable dendrites and infinite volume change associated with poor rate capabilities are stagnating its practical applications. Here, a new type of perpendicular MXene–Li array is developed with tunable MXene walls and constant space in between as anodes for lithium metal batteries. Such perpendicular MXene arrays possess dual periodic interspaces, i.e., nanometer‐scale interspaces in MXene walls and micrometer‐scale interspaces between MXene walls. The former interspaces are favorable for the fast transfer of lithium ions upon stripping and plating, and the latter enables efficiently homogenization of the electric field, leading to a good high‐rate capability up to 20 mA cm −2 . More importantly, the notorious lightning rod effect and volume change are efficiently inhibited in such perpendicular MXene arrays, giving rise to a dendrite‐free lithium anode with a low potential of 25 mV, a high capacity of 2056 mAh g −1, and good cycle stability up to 1700 h. Abstract : Dendrite‐free lithium anodes of perpendicular MXene–Li arrays with tunable MXene walls and constant space in between are produced. Such perpendicular MXene arrays possess dual periodic interspaces, i.e., nanometer‐scale interspaces in MXene walls for rapid transportation of lithium ions and micrometer‐scale interspaces between MXene walls to homogenize the electric field, inhibiting the notorious lightning rod effect, providing practical strategies for high‐energy‐density lithium‐based batteries.